Determination of inhibitory activities of enzymes, related to Alzheimer’s disease and diabetes mellitus of plane tree (Platanus orientalis L.) extracts and their antioxidant, antimicrobial and anticancer activities - Ucar, Esra; Eruygur, Nuraniye; Atas, Mehmet; Ergul, Merve; Ergul, Mustafa; Sozmen, Fazli (Cellular and Molecular Biology, 2018)
Plane tree (Platanus orientalis L.) leaves have been employed for centuries in various countries due to their pharmacological value. Therefore, determination of the biological activity of the leaves is of interest. The aim of the study was to evaluate the inhibitory effects against Alzheimer’s disease-related enzymes Acetylcholinesterase (AChE) and Butyrylcholinesterase (BuChE), diabetes mellitus related enzymes Î±-glucosidase and Î±-amylase. The antioxidant, anticancer, and antimicrobial activities of the leaves were also studied. According to the results, both water and methanol extracts of P. orientalis demonstrated more Î±-glucosidase and Î±-amylase inhibition activity than the antidiabetic drug-acarbose at the same concentration level. In addition, extracts showed good inhibition activity against AChE and BuChE. Significant results were obtained regarding antioxidant, anticancer, and antimicrobial activities. These results are very promising especially for the improvement of pharmaceutical formulations to treat various diseases such as age-related diseases, cancer, diabetes etc. and it is necessary to conduct further experiments.